Implementasi Warning Light Fire Berbasis Internet of Thing (IoT) - Abdul Muharam, Eko; Rozie, Fachrul; Chandra, Yudi (Electrical Network Systems and Sources, 2024)
Fire is a disaster that can cause major losses, especially in school environments filled with children. To improve security and quick response to fire incidents, we developed an Internet of Thing (IoT)-based "Warning Light Fire" system at the Benua Kayong 01 Elementary School. This system is designed to detect fires early and provide warnings through warning lights and notifications sent to mobile devices via the internet. The system consists of a smoke sensor and a temperature sensor connected to a microcontroller that can send data to Telegram. If the sensor detects smoke, the system will send to Telegram to notify if there is smoke, and if the temperature sensor detects signs of fire, the system will activate warning lights in the school area and send real-time notifications to the mobile devices of school staff and officers. firefighter. Test results show that this system is effective in detecting fires with a fairly fast and accurate response. The implementation of this system is expected to increase preparedness and reduce the risk of loss due to fire in schools. In the future, this system can be further developed with the integration of artificial intelligence technology for more accurate fire predictions.